British union-catalogue of periodicals : incorporating world list of scientific periodicals 2026-02-15T20:38:12+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Gascoigne J.; Porter, Kenneth I. (Butterworths, 1977)

(untitled)
"The British union-catalogue of periodicals (BUCOP) in its new form is concerned with the recording of new periodical titles for the period in and after 1960."